Innovations in Agronomic Management for Adaptation to Climate Change in Legume Cultivation - Yucel, Derya; Yucel, Celal; Kamçi, Gizem; Hamwieh, Aladdin (Taylor & Francis, 2023)
Climate change has significant impacts on agriculture and has the potential to further impact it through changing rainfall patterns, drought, floods, increases in average high temperature, and other climatic factors. The negative effects of these changes are expected to be more common than positive effects. Grain and forage legumes play an important role in agriculture by providing protein-rich food and feed. In parallel with the rapidly increasing world population, the need for food is also increasing. However, the limited possibilities of expanding the farm lands bring serious problems to agricultural production today. Until now, the only way to increase agricultural production was to obtain more products per unit area. However, the studies and methods applied in this direction bring some drawbacks. The biggest success in agriculture in the future is to achieve the desired increase in production by reducing the effect of climate change. This can only be possible with sustainable agricultural methods that will be directly helpful in promoting an appropriate production system. Developing resistant/tolerant legume crop cultivars suitable for abiotic stress conditions and wide adaptation as well as development of suitable agronomic approaches must be implemented globally. These approaches will improve the production of sufficient and quality foodstuffs, which are needed by the rapidly growing world population, at affordable costs, and the protection of the environment and natural agricultural resources.